2011
DOI: 10.1183/09031936.00130310
|View full text |Cite
|
Sign up to set email alerts
|

Renin is an angiotensin-independent profibrotic mediator: role in pulmonary fibrosis

Abstract: The pathogenesis of idiopathic pulmonary fibrosis (IPF) is probably the result of interplay between cytokines/chemokines and growth factors. The renin-angiotensin (Ang) system is involved, although its profibrotic effect is attributed to Ang II. However, recent studies suggest that renin, through a specific receptor, is implicated in fibrogenesis.In this study, the expression of renin and renin receptor was examined in normal and IPF lungs and fibroblasts. Normal human lung fibroblasts were stimulated with ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Collagen measurement. Collagen was quantified in cell-conditioned medium using the Sircol collagen assay (Biocolor, Belfast, UK) as described (29).…”
Section: Methodsmentioning
confidence: 99%
“…Collagen measurement. Collagen was quantified in cell-conditioned medium using the Sircol collagen assay (Biocolor, Belfast, UK) as described (29).…”
Section: Methodsmentioning
confidence: 99%
“…From another perspective, Molteni et al (83) showed that Ang II receptor inhibitors were helpful in palliating RILI. Additionally, certain researchers suggested renin as a profibrotic mediator independent from the angiotensin system, in the lung and other organs, which may provide another approach to mitigating lung fibrosis (84,85). …”
Section: Treatmentsmentioning
confidence: 99%
“…Collagen concentration was determined by colorimetric Sircol soluble collagen assay (Biocolor Ltd., Carrickfergus, UK) according to the manufacturer's instructions [22]. Optical density was measured at 555 nm using an ELISA plate reader (Sinergy HT, BioTek).…”
Section: Collagen Assaymentioning
confidence: 99%